Tolerance of fry of three tilapia varieties exposed to low temperatures - Rezende, Cicero Eduardo de; Fernandes, Diana Carla Oliveira; Marcal, Danielle Cristina Pereira; Neto, Rafael Vilhena Reis [UNESP]; Paulino, Renan Rosa; Freitas, Rilke Tadeu Fonseca de (Inst Federal Sul Minas Gerais-i Fsuldeminas, 2024)
Tilapia are known for their tolerance to wide ranges of water quality, diets and farming systems. However, their performance is affected in countries with harsh winters, with almost zero growth, high mortality and consequently low economic efficiency during this period. In view of the above, this study was developed with the aim of evaluating the cold tolerance of fry from three contemporary groups of three varieties of tilapia, two commercial varieties and one local variety (MGTUP), developed by the Federal University of Lavras. A total of 3,240 animals were used, distributed according to age in three tanks. The experimental design was a completely randomized factorial arrangement, consisting of nine treatments (3 contemporary groups x 3 genetic groups) with three repetitions per treatment. During the experimental period, daily evaluations were carried out to count mortality, measure water temperature and dissolved oxygen levels. The fish survival time data (in days) was submitted to multivariate Cox regression to evaluate the effects of genetic groups and contemporaries, and their interactions on survival time. Older fry are more resistant to cold stress. Notably, the MGTUP variety is cold tolerant, with survival rates close to 90 %, and is superior in all age groups. These findings suggest that the use of tilapia varieties adapted to the climate of the region where they will be grown may significantly mitigate losses in aquaculture, especially in regions prone to cold.
Keywords: Cold Resistance; Fingerlings; Genetic Groups; Oreochromis niloticus